2002
DOI: 10.1063/1.1386669
|View full text |Cite
|
Sign up to set email alerts
|

Ionization energy studies for ozone and OClO monomers and dimers

Abstract: Electron impact ionization cross sections measured close to threshold are reported for both the monomers and dimers of ozone and OClO using a new high resolution electron impact apparatus. The present appearance energies AE͑O 3 ϩ /O 3 ͒ϭ12.70Ϯ0.02 eV, AE ͑OClO ϩ /OClO͒ϭ10.55Ϯ0.02 and AE͑ClO ϩ /OClOϭ13.37Ϯ0.03 eV derived from the measured ionization cross sections are in excellent agreement with the vertical threshold values determined for these ions by high resolution PES and PIMS photoionization studies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
6
14
1
Order By: Relevance
“…This is consistent with the change in bond lengths calculated for OIO + The zero-point vibrational energy corrected adiabatic ionization potentials (AIPs) calculated for the OXO (X=Cl, Br, and I) are listed in Table 3 along with the experimental AIP values of OClO and OBrO. [18][19][20][21] Since the experimental value is available for OClO and OBrO, consider the calculated AIPs for OClO and OBrO first. The AIPs calculated at the HF and B3LYP levels overestimate the experimental value of OClO by 22 and 44 kJ/mol, respectively.…”
Section: Resultssupporting
confidence: 48%
“…This is consistent with the change in bond lengths calculated for OIO + The zero-point vibrational energy corrected adiabatic ionization potentials (AIPs) calculated for the OXO (X=Cl, Br, and I) are listed in Table 3 along with the experimental AIP values of OClO and OBrO. [18][19][20][21] Since the experimental value is available for OClO and OBrO, consider the calculated AIPs for OClO and OBrO first. The AIPs calculated at the HF and B3LYP levels overestimate the experimental value of OClO by 22 and 44 kJ/mol, respectively.…”
Section: Resultssupporting
confidence: 48%
“…18 In that work, the stable structure of O 6 (and also O 8 ) was not found at the DFT level (B3LYP and B3PW91 with conjunction 6-31G* and 6−311G(2df) basis sets) but was optimized using the MP2 calculations, although the corresponding energies and structural data were not reported. In the experimental and theoretical study of Probst et al, 48 it was also reported that MP2/6-311G* calculations were performed for O 6 (and MP2/DZP for O 8 ) without detailed presentation of the calculation data. In 2002, there was a report 49 that the O 6 and O 9 ozone clusters were optimized at the PM3 level and using the MP4/6-311++G(d,p) and QCISD/6-311++G(d,p) potential curve calculations.…”
Section: Introductionmentioning
confidence: 99%
“…5. Spectroscopic and theoretical studies of the ozone dimer (Slanina and Adamowicz, 1993;Bahou et al, 2001;Probst et al, 2002;Sander et al, 2006) indicate the ozone dimer photolysis cross section is much smaller than that of the monomer, and recent molecular beam studies by show the weak intermolecular interactions are not strong enough to affect the absorption spectra of the monomer. In addition, notes in his review that there is no experimental or theoretical evidence of pressure dependence in the O 3 cross section in the region of interest.…”
Section: Pressure and Relative Humidity Effect On Omentioning
confidence: 99%